TorakochirurgiaLeiomyoma of the oesophagus - Włodarczyk, Janusz; Olechnowicz, Henryk; Kocoń, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: Oesophageal leiomyomas are the most common benign tumours of the oesophagus. This pathology is most frequently detected during endoscopy of the upper gastrointestinal tract. Occasionally, these oesophageal leiomyomas can undergo malignant transformation. Aim: The analysis included 18 patients in whom complications following enucleation of oesophageal leiomyoma were assessed and then evaluation of the safety and effectiveness of the employed treatment was performed. Material and Methods: Patients qualified for surgery were operated on using right side thoracotomy. All patients were intubated using a double lumen tube and operated on with the right lung inactivated. Preoperational microscopic verification was not obtained from all patients. During the operation, endoscopy of the oesophagus was conducted, which facilitated especially the localization of small changes and made it possible to confirm the tightness of the oesophageal walls after leiomyoma enucleation and suturing of its muscular aspect. Results: 18 patients who were treated in the unit in the years 1990 – 2006 were analyzed. Complications such as leakage of oesophageal walls, mediastinitis and postoperative death did not occur in these patients. Oesophageal resection was not performed in any of these cases. In long-term observation, no recurrence has been observed nor any malignancy. The average stay in the unit was 8 days. Conclusions: Enucleation of oesophageal leiomyoma is a safe procedure. Selection of the most suitable technique of the operation depends on the experience of the particular surgical facility.